2015
DOI: 10.1007/s00011-015-0891-0
|View full text |Cite
|
Sign up to set email alerts
|

2-Amino-4-(3,4-(methylenedioxy)benzylamino)-6-(3-methoxyphenyl)pyrimidine is an anti-inflammatory TLR-2, -4 and -5 response mediator in human monocytes

Abstract: Objective and design To elucidate the influence of 2-amino-4-(3,4-(methylenedioxy)benzylamino)-6-(3-methoxyphenyl)pyrimidine (AMBMP), a canonical Wnt/β-catenin pathway activator, on the inflammatory response of TLR-engaged innate cells in vitro. Material or subject Primary human monocytes. Treatment AMPMB (0–10 μM), LPS (0–1.0 μg/ml), Pam3CSK4, FSL-1, or S. typhimurium flagellin (0–0.25 μg/ml). Methods TLR-induced cytokine release (TNF, IL-6, IL-12 p40) was monitored by ELISA while Wnt-related signals (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Moreover, the downstream responders of canonical Wnt3a signaling, GSK3β-β-catenin, can suppress bacterial-induced inflammation through the binding of β-catenin to NF-κB (21)(22)(23). We and others have demonstrated that Wnt3a canonical signaling restrains TLR4-mediated inflammation in innate immune cells (24)(25)(26)(27). Further, the expression of Wnt3a and its suppressor, DKK1, has been reported to be associated with the progression of inflammation and is also involved in periodontal disease (26,28).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, the downstream responders of canonical Wnt3a signaling, GSK3β-β-catenin, can suppress bacterial-induced inflammation through the binding of β-catenin to NF-κB (21)(22)(23). We and others have demonstrated that Wnt3a canonical signaling restrains TLR4-mediated inflammation in innate immune cells (24)(25)(26)(27). Further, the expression of Wnt3a and its suppressor, DKK1, has been reported to be associated with the progression of inflammation and is also involved in periodontal disease (26,28).…”
Section: Introductionmentioning
confidence: 91%
“…Since Wnt3a has been demonstrated to suppress TLR-mediated inflammation (20,27,45,46) in monocytes or macrophages, we next examined whether Wnt3-mediated GSK3β-βcatenin signaling restrains P. gingivalis-induced inflammatory responses. We found that siRNA-mediated Wnt3a or Dvl3 silencing led to a significant increase in the production of inflammatory cytokines, including TNFα, IL-6, and IL-12P40, in P. gingivalis-stimulated monocytes (Fig.…”
Section: Jak3-mediated Wnt3a-β-catenin Signaling Suppresses Productio...mentioning
confidence: 99%
“…Among these types of compounds, it is worth mentioning the cell permeable small molecule AMBMP that is a recognized canonical Wnt/b-catenin activator, the g-secretase and notch inhibitor DAPT, and the novel benzoxazole derivative K313 with immunosuppressive activity toward T cell proliferation. They all inhibit the activity of GSK3b by increasing the relative abundance of phospho-GSK3b-Ser9 (82)(83)(84). (Table S1), suggesting that these molecules may be used as effective GSK3b inhibitors of LPS-induced inflammation.…”
Section: Compounds Designed To Selectively Inhibit Proteins Structurally Unrelated To Gsk3bmentioning
confidence: 99%
“…Accordingly, its downstream component β-Catenin was down-regulated (figure 5D). Whereas, an activator of β-Catenin21 reversed the effect of both miR-424–5p and let-7d-5p mimics on induction of MET in HELF cells (figure 5E). Noted of, FLCN knockdown alone in HELF cells did not show WNT signalling disruption (see online supplementary figure S2), yet both miR-424–5p and let-7d-5p mimics did, and importantly, both mimics worked in the condition of FLCN knockdown (see online supplementary figure S4).…”
Section: Resultsmentioning
confidence: 96%